Multifunctional carbon dioxide-based elastomer as well as preparation method and application thereof
A self-healing, reconfigurable carbon dioxide-based elastomer was prepared by ternary copolymerization of carbon dioxide, propylene oxide, and allyl glycidyl ether, combined with a thermally initiated reverse vulcanization reaction of bio-based small molecule lipoic acid. This solved the functional limitations and resource waste problems of existing CO2-based polycarbonates, and enabled the application of highly efficient self-healing and degradable materials.
Patent Information
- Application Number
- CN202511205348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-02
AI Technical Summary
The types of CO2-based polycarbonates currently available are limited, their glass transition temperatures are close to room temperature, they have poor dimensional stability, lack reactive functional groups, and their functions and applications are limited. Furthermore, the irreversible nature of traditional chemical crosslinking leads to resource waste and decreased biodegradability.
A carbon dioxide-based elastomer based on disulfide bond crosslinking was prepared by ternary copolymerization of carbon dioxide, propylene oxide, and allyl glycidyl ether, followed by thermally initiated reverse sulfurization reaction of bio-based small molecule lipoic acid. This elastomer achieves self-healing, reprocessing, and autocatalytic degradation.
A multifunctional carbon dioxide-based elastomer was prepared, which has self-healing reinforcement, reprocessing and reconfigurable shape memory functions, with a glass transition temperature in the range of 10-25℃. The dynamic disulfide bond crosslinking network improves the reconfigurability and degradation efficiency of the material.
Smart Images

Figure CN121045531A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of polymer material preparation, specifically to a multifunctional carbon dioxide-based elastomer, its preparation method, and its applications. Background Technology
[0002] Carbon dioxide (CO2) is one of the most basic carbon sources, abundant, inexpensive, and non-toxic, making it an ideal raw material for chemical synthesis. Carbon dioxide-based polycarbonates, prepared by reacting carbon dioxide as a comonomer with epoxides, possess biodegradability and diverse properties, contributing not only to reducing atmospheric CO2 concentrations but also mitigating white pollution. However, the variety of CO2-based polycarbonates is currently limited. The main commercially available polypropylene carbonate has a glass transition temperature close to room temperature and poor dimensional stability. Furthermore, its functionality and applications are restricted across various fields due to the lack of reactive functional groups. Therefore, the development of novel CO2-based polymer materials is urgently needed.
[0003] By copolymerizing flexible epoxides with reactive functional groups with carbon dioxide, CO2-based elastomer materials can be prepared, expanding the application of CO2 in the field of elastomers. For example, Paolo P et al. copolymerized carbon dioxide with long alkyl chains (C6-C6) to... 12 A ternary copolymerization of cumene peroxide and unsaturated epoxides was used to synthesize polycarbonate elastomers with low glass transition temperatures, and dicumyl peroxide was used as a crosslinking agent to enhance their properties [Green Chem., 2023, 25, 7612-7626]. However, the traditional chemical crosslinking obtained by this method is irreversible; once the material is damaged, it cannot be repaired or reprocessed, resulting in resource waste. Furthermore, permanent crosslinking reduces its biodegradability.
[0004] Introducing dynamic covalent crosslinking into elastomers can overcome the problems of traditional elastomers' difficulty in healing and reprocessing, while also endowing elastomers with functionality [Science, 2017, 356, 62-65; Chem. Sci., 2016, 7, 30; Matter 5, 1391–1422, May 4, 2022], and has become a research hotspot in the field of polymer materials. However, there are no reports on dynamically covalently crosslinked CO2-based elastomers, and there is no multifunctional dynamically covalently crosslinked CO2-based elastomer that integrates self-healing reinforcement, reprocessing, autocatalytic degradation, and reconfigurable shape memory functions, nor its preparation method and application. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention proposes a multifunctional carbon dioxide-based elastomer, its preparation method, and its applications. A ternary copolymer with a double bond structure is prepared by ternary copolymerization of carbon dioxide (CO2), propylene oxide (PO), and allyl glycidyl ether (AGE). The carbon dioxide-based elastomer, based on disulfide bond crosslinking, is obtained through a thermally initiated reverse vulcanization reaction using bio-based small molecule lipoic acid.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A multifunctional carbon dioxide-based elastomer is a carbon dioxide-based elastomer obtained by copolymerizing carbon dioxide, propylene oxide and allyl glycidyl ether to obtain a ternary copolymer with double bond structures in the side chain, and by thermally initiating a reverse vulcanization reaction of bio-based small molecule thioctic acid, which is based on disulfide bond crosslinking.
[0008] Furthermore, the structural formula of the ternary copolymer with double bond structure in the side chain is as follows: wherein the number average molecular weight is not less than 10 kDa, the content of carbon-carbon double bonds is 5-15 mol%, the content of polyether is less than 10 mol%, and x, y, z > 0;
[0009]
[0010] Furthermore, the preparation method of the above-mentioned multifunctional carbon dioxide-based elastomer includes the following steps:
[0011] (1) In a catalytic system suitable for carbon dioxide-epoxide copolymerization, the reactants propylene oxide, allyl glycidyl ether, and catalyst were added to a high-pressure reactor. The reactor was then sealed, and the air inside was replaced with carbon dioxide while maintaining the set pressure. The temperature was then raised to initiate the ring-opening copolymerization reaction. After the reaction was complete, the product was dissolved in a good solvent, and an excess of a poor solvent was added to precipitate the product. The dissolution and precipitation process was repeated to obtain a terpolymer with double bonds in the side chains.
[0012] (2) Dissolve the terpolymer with double bond structure in the side chain and thioctic acid in a solvent, add a free radical initiator, and hot press at high temperature after the solvent has completely evaporated. Crosslink the terpolymer through the "reverse vulcanization" reaction initiated by the free radical initiator to obtain a multifunctional carbon dioxide-based elastomer.
[0013] Furthermore, the catalyst is a metal carboxylate, a bimetallic cyanide, or a metal Salen complex, and the volume / mass ratio of propylene oxide to the catalyst is 15–40 mL / g.
[0014] Furthermore, the molar ratio of allyl glycidyl ether to propylene oxide is 1:(4-20).
[0015] Furthermore, the set pressure of carbon dioxide introduced during the ring-opening copolymerization reaction is 3-5.0 MPa, the reaction temperature is 60-80℃, and the reaction time is 24-40 h.
[0016] Furthermore, the mass ratio of the thioctic acid to the terpolymer containing double bonds in the side chain is 1:(6-20).
[0017] Furthermore, in step (2), the concentration of the mixed solution of the terpolymer and thioctic acid is 5-20 mL / g, the good solvent is one or more of tetrahydrofuran, dichloromethane, and chloroform, the bad solvent is methanol or ethanol, the hot pressing time is 10-30 min, and the hot pressing temperature is 120-140℃.
[0018] Furthermore, in step (2), the free radical initiator is one or a combination of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the free radical initiator to the terpolymer is 1:100.
[0019] The aforementioned multifunctional carbon dioxide-based elastomer is applied in the fields of general elastomers, flexible electronics, adhesives, biomedicine, and green packaging.
[0020] The beneficial effects of this invention are as follows: This invention utilizes bio-based small molecule lipoic acid to crosslink a terpolymer of carbon dioxide (CO2), propylene oxide (PO), and allyl glycidyl ether (AGE) via a thermally activated reverse vulcanization reaction to prepare a multifunctional carbon dioxide-based elastomer material integrating self-healing reinforcement, reworkability, autocatalytic degradation, and reconfigurable shape memory functions. The preparation process of this invention is simple and expands the prospects for high-value utilization of CO2 resources.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) This invention uses carbon dioxide as the main raw material and bio-based small molecule lipoic acid as a crosslinking agent, which has the advantages of being green, low-carbon and renewable.
[0023] (2) The carbon dioxide-based elastomer of the present invention is prepared by lipoic acid through a reverse sulfurization reaction. It not only constructs a dynamic covalent network of disulfide bond crosslinking, giving the elastomer self-healing and reshaping capabilities, but also introduces a large number of carboxyl groups, which can act as an internal catalyst to catalyze the degradation of the elastomer, thus overcoming the problem of slow degradation rate of bio-based polyesters.
[0024] (3) The carbon dioxide-based elastomer of the present invention exhibits self-healing and enhanced properties, with a healing efficiency of up to 160%.
[0025] (4) The glass transition temperature of the carbon dioxide-based elastomer of the present invention is in the range of 10-25°C. Combined with the reshaping ability given by dynamic disulfide bonds, it exhibits a reconfigurable and body temperature-driven shape memory effect. Attached Figure Description
[0026] The accompanying drawings are provided to further illustrate and explain the technical solutions and embodiments of the present invention, and do not constitute a limitation thereof. In the drawings:
[0027] Figure 1 The image shows the 1H NMR spectrum of the terpolymer obtained in Example 1.
[0028] Figure 2 The infrared absorption spectra of Example 1 and Comparative Example 1 are shown.
[0029] Figure 3 This is a photograph of the experiment in Example 1 after swelling in dichloromethane solvent for 48 hours.
[0030] Figure 4 The tensile stress-strain curves are for Examples 1 / 5 / 6 and Comparative Example 1.
[0031] Figure 5 These are before and after photos of self-healing in Example 6.
[0032] Figure 6 The stress-strain curves are for Example 6 and Self-Healing Example 1.
[0033] Figure 7 The stress-strain curves before and after self-healing are shown for Comparative Example 2 and Self-Healing Example 2.
[0034] Figure 8 The composting degradation of Example 6 and Comparative Example 1 at different number of days is shown.
[0035] Figure 9 This is a schematic diagram of the synthetic route for the multifunctional carbon dioxide-based elastomer of the present invention. Detailed Implementation
[0036] The present invention will now be described in detail with reference to specific test examples. It should be noted that the following test examples are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0037] This invention provides a multifunctional carbon dioxide-based elastomer, its preparation method, and its application. The method is achieved through the following steps:
[0038] A ternary copolymer with a double bond structure was prepared by ternary copolymerization of carbon dioxide (CO2), propylene oxide (PO) and allyl glycidyl ether (AGE). A carbon dioxide-based elastomer based on disulfide bond crosslinking was obtained by thermally initiated reverse vulcanization reaction of bio-based small molecule lipoic acid.
[0039] Example 1
[0040] (1) Weigh 0.3g of zinc glutarate catalyst and place it in a dry high-pressure reactor. Dry under vacuum, and replace the air in the reactor three times with nitrogen. Inject 10mL of propylene oxide and 4g of allyl glycidyl ether (the molar ratio of propylene oxide to allyl glycidyl ether is 4:1; the volume / mass ratio of propylene oxide to zinc glutarate catalyst is 33mL / g) under vacuum. Replace the gas in the reactor three times with carbon dioxide to maintain the pressure at 5.0MPa. React at 60℃ for 24h. After the reaction, wait for the reactor to cool to room temperature, slowly release carbon dioxide to atmospheric pressure, and open the reactor. Dissolve the polymer in dichloromethane, precipitate the product in excess ethanol, and repeat the dissolution and precipitation process to obtain a terpolymer. (2) Add lipoic acid to the terpolymer at a mass ratio of 20:1. Dissolve 10g of the terpolymer and lipoic acid in 100mL of dichloromethane (the concentration of the mixed solution of terpolymer and lipoic acid is 10mL / g). Add 1wt% of the initiator azobisisobutyronitrile (AIBN) according to the mass of the terpolymer. After mixing evenly, place the mixture in a fume hood to evaporate the solvent. After the solvent has completely evaporated, hot press at 120℃ for 20min to obtain a carbon dioxide-based elastomer with disulfide bond crosslinking.
[0041] Example 2
[0042] The specific process is the same as in Example 1, except that the amount of allyl glycidyl ether added in step (1) is changed to 0.82g (the molar ratio of propylene oxide to allyl glycidyl ether is 20:1), the amount of zinc glutarate catalyst is changed to 0.25g (the volume / mass ratio of propylene oxide to zinc glutarate catalyst is 40mL / g), the reaction temperature is 70℃, and the reaction time is 30h.
[0043] Example 3
[0044] The specific process is the same as in Example 1, except that the amount of allyl glycidyl ether added in step (1) is changed to 2.5g (the molar ratio of propylene oxide to allyl glycidyl ether is 6.7:1), the amount of zinc glutarate catalyst is changed to 0.40g (the volume / mass ratio of propylene oxide to zinc glutarate catalyst is 25mL / g), the carbon dioxide pressure is 4MPa, and the reaction temperature is 80℃.
[0045] Example 4
[0046] The specific process is the same as in Example 1, except that the amount of allyl glycidyl ether added in step (1) is changed to 3.2g (the molar ratio of propylene oxide to allyl glycidyl ether is 5:1), the amount of zinc glutarate catalyst is changed to 0.67g (the volume / mass ratio of propylene oxide to zinc glutarate catalyst is 15mL / g), the carbon dioxide pressure is 3MPa, and the reaction time is 40h.
[0047] Example 5
[0048] The specific process is the same as in Example 1, except that the catalyst in step (1) is replaced with a Zn-Co DMC catalyst.
[0049] Example 6
[0050] The specific process is the same as in Example 1, except that the catalyst in step (1) is replaced with Salen-Co(Ⅲ) catalyst.
[0051] Example 7
[0052] The specific process is the same as in Example 1, where the terpolymer in step (2) is reacted with thioctic acid at a mass ratio of 6:1.
[0053] Example 8
[0054] The specific process is the same as in Example 1, where the terpolymer in step (2) is reacted with thioctic acid at a mass ratio of 10:1.
[0055] Example 9
[0056] The specific process is the same as in Example 1. In step (2), the concentration of the mixed solution of terpolymer and thioctic acid is 5 mL / g, the hot pressing time is 10 min, and the hot pressing temperature is 140℃.
[0057] Example 10
[0058] The specific process is the same as in Example 1. In step (2), the concentration of the mixed solution of terpolymer and thioctic acid is 20 mL / g, the hot pressing time is 30 min, and the hot pressing temperature is 130 °C.
[0059] Comparative Example 1
[0060] The specific process is the same as in Example 8. After dissolving 10g of the terpolymer in step (1) in 100mL of dichloromethane, without adding the initiator AIBN and thioctic acid, hot press at 120℃ for 20min.
[0061] Comparative Example 2
[0062] The specific process is the same as in Example 8, except that thioctic acid is not added in step (2), and the mixture is hot-pressed at 120°C for 20 minutes.
[0063] Self-healing example 1
[0064] The disulfide-crosslinked carbon dioxide-based elastomer prepared in Example 8 was cut into two segments with a blade and then allowed to heal at 60°C for 24 hours.
[0065] Self-healing example 2
[0066] The self-crosslinked carbon dioxide-based elastomer prepared in Comparative Example 2 was cut into two segments with a blade and then allowed to heal at 60°C for 24 hours.
[0067] Figure 1 The NMR spectrum of the ternary copolymer polycarbonate in Example 1 confirms the successful synthesis of polycarbonate with double bond structures in the side chains. The peaks at 5.8 ppm and 5.1–5.3 ppm correspond to allyl groups (-CH ═ CH2), the absorption peaks at 4.2 ppm and 5.0 ppm are attributed to CH2 and CH in the carbonate unit, respectively, and the peak at 3.4–3.7 ppm corresponds to ether bonds.
[0068] Table 1
[0069]
[0070] Table 1 shows the quantitative analysis of double bond and ether bond content in the products using 1H NMR spectroscopy and the specific values of their number-average molecular weight determined using gel permeation chromatography (GPC). The molar content of double bonds in the terpolymer showed a good correlation with the monomer feed ratio. The double bond content in Examples 1–4 ranged from 5.2% to 12.6%, while the ether bond content, as a byproduct, was controlled below 10%. The number-average molecular weight of the copolymers prepared in all examples was above 62 kg / mol, with the highest reaching 73 kg / mol (Example 4).
[0071] Figure 2 The figures show the infrared spectra of polycarbonate samples before and after disulfide crosslinking in Example 1. As can be seen from the figures, compared to the spectra of the polycarbonate sample before crosslinking, the spectra of the sample after crosslinking show a higher concentration at 1606 cm⁻¹. -1 and 1621cm -1 The reduced peak intensity of the C=C stretching vibration of the olefin indicates that the sulfur free radicals generated by the ring-opening of lipoic acid react with the side alkenyl groups of polycarbonate, introducing dynamic disulfide bonds to form a dynamic cross-linking network. Figure 3 An equilibrium swelling experiment was conducted by immersing the sample in dichloromethane for 48 hours. It was found that the sample only swelled but did not dissolve in dichloromethane, indicating that the sample was successfully cross-linked and formed a covalent cross-linked network structure.
[0072] Table 2
[0073]
[0074] Table 2 shows the gel fraction, glass transition temperature, and thermal decomposition temperature of the samples. The highest gel fraction, reaching 65°C, was observed in Example 1. With changes in the amount of thioctic acid added and the hot-pressing conditions, the gel fraction did not change significantly, generally remaining between 59% and 65%. The T values of Examples 1 / 7 / 8 / 9 / 10 after crosslinking... g All showed varying degrees of improvement, with the highest reaching 18°C (Example 1). This is because the formation of the cross-linked network restricts the movement of polymer chain segments, requiring the material to reach a higher temperature for the glass transition; the thermal decomposition temperature (T) of Comparative Example 1... d The thermal stability is only 150℃, indicating poor thermal stability. In contrast, the thermal decomposition temperatures of crosslinked Examples 1 / 7 / 8 / 9 / 10 are all increased. Compared to Comparative Example 1, the thermal decomposition temperatures of the embodiments of the present invention are significantly higher. d The value increased by at least 66°C, and by a maximum of 87°C (Example 1).
[0075] Figure 4 The stress-strain curves of the samples before and after crosslinking are shown. Compared with Comparative Example 1, the strength and toughness of the sample after crosslinking are improved to varying degrees.
[0076] Table 3
[0077] Sample Name Tensile strength (MPa) Elongation at break (%) Young's modulus (MPa) Comparative Example 1 1.5±0.1 925±83 7.0±0.3 Example 1 3.0±0.1 1051±92 6.2±0.1 Example 7 2.1±0.1 987±39 5.6±0.1 Example 8 2.5±0.1 1118±35 5.4±0.1
[0078] Table 3 shows the specific values of tensile strength, elongation at break, and Young's modulus of cross-linked polycarbonates containing different mass fractions of thioctic acid.
[0079] Figure 5 These are photos of the cross-linked sample before and after self-healing in Example 8. Figure 6 The stress-strain curves of dynamically cross-linked polycarbonate in Example 8 and self-healing Example 1 at 60°C for different healing times are shown. As the healing time increases, the tensile strength and elongation at break gradually increase, almost the same as the original sample. The strength of the sample after 24 hours of healing exceeds that of the original sample. Figure 7 The stress-strain curves of the self-crosslinked polycarbonate in Comparative Example 2 and Self-Healing Example 2 after healing at 60°C for 24 hours show that it does not have self-healing ability. Figure 8 The composting degradation of Example 8 and Comparative Example 1 at different number of days is shown. Compared with Comparative Example 1, the degradation rate of Example 8 is faster, indicating that the carboxyl group in the lipoic acid structure can act as a self-catalyst to accelerate the degradation of the sample.
Claims
1. A multifunctional carbon dioxide-based elastomer, characterized in that, The multifunctional carbon dioxide-based elastomer is a ternary copolymer with double bond structures in the side chains obtained by copolymerization of carbon dioxide, propylene oxide and allyl glycidyl ether, and a carbon dioxide-based elastomer based on disulfide bond crosslinking obtained by thermal initiation of desulfurization reaction of bio-based small molecule lipoic acid.
2. The multifunctional carbon dioxide-based elastomer as described in claim 1, characterized in that, The structural formula of the ternary copolymer with double bond structure in the side chain is shown below: wherein the number average molecular weight is not less than 10 kDa, the content of carbon-carbon double bonds is 5-15 mol%, the content of polyether is less than 10 mol%, and x, y, z > 0; 3. A method for preparing a multifunctional carbon dioxide-based elastomer according to any one of claims 1 to 2, characterized in that, Includes the following steps: (1) In a catalytic system suitable for carbon dioxide-epoxide copolymerization, the reactants propylene oxide, allyl glycidyl ether and catalyst are added to a high-pressure reactor, the reactor is sealed, the air inside the reactor is replaced with carbon dioxide and the pressure is maintained at the set point, and the ring-opening copolymerization reaction is started by heating; after the reaction is completed, the product is dissolved with a good solvent, and an excess of poor solvent is added to precipitate the product; the dissolution and precipitation process is repeated to obtain a ternary copolymer with double bond structure in the side chain; (2) Dissolve the terpolymer with double bond structure in the side chain and thioctic acid in a solvent, add a free radical initiator, and hot press at high temperature after the solvent has completely evaporated. Crosslink the terpolymer through the "reverse vulcanization" reaction initiated by the free radical initiator to obtain a multifunctional carbon dioxide-based elastomer.
4. The method for preparing the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, The catalyst is a metal carboxylate, a bimetallic cyanide, or a metal Salen complex, and the volume / mass ratio of propylene oxide to the catalyst is 15–40 mL / g.
5. The method for preparing the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, The molar ratio of allyl glycidyl ether to propylene oxide is 1:(4-20).
6. The method for preparing the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, The set pressure of carbon dioxide introduced during the ring-opening copolymerization reaction is 3-5.0 MPa, the reaction temperature is 60-80℃, and the reaction time is 24-40 h.
7. The method for preparing the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, The mass ratio of the thioctic acid to the terpolymer containing double bonds in the side chain is 1:(6-20).
8. The method for preparing the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, In step (2), the concentration of the mixed solution of terpolymer and thioctic acid is 5-20 mL / g, the good solvent is one or more of tetrahydrofuran, dichloromethane, and trichloromethane, the bad solvent is methanol or ethanol, the hot pressing time is 10-30 min, and the hot pressing temperature is 120-140℃.
9. The preparation method of the multifunctional carbon dioxide-based elastomer as described in claim 3, characterized in that, In step (2), the free radical initiator is one or a combination of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the free radical initiator to the terpolymer is 1:
100.
10. The application of a multifunctional carbon dioxide-based elastomer according to any one of claims 1-2, or a multifunctional carbon dioxide-based elastomer prepared by the preparation method according to any one of claims 3-9, characterized in that, Applications include general elastomers, flexible electronics, adhesives, biomedicine, and green packaging.